Transporter protein genes are differentially expressed in Acidithiobacillus ferrooxidans LR maintained in contact with covellite - Reis, Fernanda C.; Madureira, Danielle J.; Vicentini, Renato; Carlos, Camila; Ferraz, Lucio F. C.; Garcia, Oswaldo [UNESP]; Ottoboni, Laura M. M. (Springer, 2010)
Gene expression in response to the copper sulfide, covellite (CuS), in Acidithiobacillus ferrooxidans LR was investigated by using RNA arbitrarily primed polymerase chain reaction (RAP-PCR). Seven genes that encode for proteins involved with transport and binding were up-regulated in the presence of CuS. The differential expression of the seven genes was confirmed by real-time PCR. An atomic absorption analysis of the covellite samples showed that the quantity of copper(II) ions in solution changed from zero to approximately 1.11 g/l after 24 h, and the pH changed from 1.8 to 4.0, suggesting that the copper ions in solution and the pH alteration may be responsible, at least in part, for the up-regulation of the transporter genes in the presence of covellite. An in silico protein-protein interaction analysis of the proteins encoded by the seven transporter protein genes, as well as of proteins encoded by genes of the same functional category that are adjacent to the seven genes identified by RAP-PCR, showed that besides the correlated function, the transporter proteins may act in different steps of the bacterial response to covellite.
Keywords: Acidithiobacillus ferrooxidans; Covellite; Gene expression; Transporter protein genes